Reflections on the Testimonial Practice About the Clandestine Detention Experience in Argentina - Messina, Luciana (Sociedad y Economía, 2012)
The objective of this work is to analyze the testimonial practice concerning the clandestine detention experience by reconstructing and analyzing the testimonial course of a survivor of a clandestine detention center during the latest military dictatorship in Argentina (1976-1983). One constant concern throughout this reconstruction has to do with understanding the gradual transformation of the discourse on crimes of state terrorism over the past thirty years. To this end, I will connect testimonial practice to different social and political situations, paying special attention to what is usually said and silenced in testimonies.